Research application of session-RPE in monitoring the training load of elite endurance athletes - Yang, Shengjie; Yin, Yiquan; Qiu, Zhaoyi; Meng, Qingjun (Frontiers in Neuroscience, 2024)
Purpose: TRIMP and sRPE are both representative indicators of training load(TL), and the correlation between two has been widely demonstrated across various sports. The aim of this study was to investigate the reliability of sRPE-TRIMP correlation across different intensities/duration of training in cross-country skiing, and whether sRPE can serve as an validity supplement to TRIMP data in cases of lost heart rate data. Method: 10 athletes were used as the experimental objects. The intensity, duration and RPE of 273 different types of training sessions were collected, and statistical methods were used for data analysis. Results: 1. There was a significant correlation between sRPE and TRIMP (r=0.68, P<0.05), but the correlation differs among the LIT, MIT and HIT groups (r=0.70, 0.46, r=0.31 , P<0.05) 2. sRPE-TRIMP correlation among three different time duration in the LIT group (0-60min, 60-120min and 120-180min), are all highly significant(r= 0.70, 0.67, 0.69, P<0.05) and the LRsRPE-TRIMP of 3 duration have no significant differences(chow test, p＞0.05). 3. The difference in actual training duration between samples was the main reason for the difference in the application effect of sRPE, because the actual training duration ratio of LIT was 89.7 ± 16.4%; MIT, 98.5 ± 6.2%; and HIT, 94.4 ± 13.5%.Conclusions: 1. The linear relationship between sRPE and TRIMP(LRsRPE-TRIMP) is more significant in LIT compared to that in MIT and HIT. 2. Variations in the duration of LIT sessions do not affect the consistency of the relationship between sRPE and TRIMP. 3.Discrepancies between actual and planned training durations directly impact the significance of the LRsRPE-TRIMP.